Optimal Contract Pricing of Distributed Generation in Distribution Networks - Maria Lopez-Lezama, Jesus; Padilha-Feltrin, Antonio [UNESP]; Contreras, Javier; Ignacio Munoz, Jose (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper proposes a bilevel programming approach to determine the optimal contract price of dispatchable distributed generation (DG) units in distribution systems. Two different agents are considered in the model, namely, the distribution company (DisCo) and the owner of the DG. The former seeks the minimization of the payments incurred in attending the forecasted demand, while the latter seeks the maximization of his profit. To meet the expected demand, the DisCo has the option to purchase energy from any DG unit within its network and directly from the wholesale electricity market. A traditional distribution utility model with no competition among DG units is considered. The proposed model positions the DG owner in the outer optimization level and the DisCo in the inner one. This last optimization problem is substituted by its Karush-Kuhn-Tucker optimality conditions, turning the bilevel programming problem into an equivalent single-level nonlinear programming problem which is solved using commercially available software. Tests are performed in a modified IEEE 34-bus distribution network.
Keywords: Bilevel programming; distributed generation; distribution networks